Development of seed analyses by means of various matrix solutions and the MALDI-TOF MS technique - Bojté, Csilla; Lovász, Csaba; Tímár, Eszter; Lajkó, László; Nagy, János; Nagy, Nikoletta Edit; Bodnár, Karina; Czerődiné Kempf, Laura; Horváth, Brigitta; Micsinai, Adrienn; Tóth, Szilárd (Acta Agraria Debreceniensis, 2019)
The earth's population is growing steadily, currently accounting for about 7.3 billion people. Population growth causes food demand to rise, approximately 36 million people die each year due to starvation or related diseases. One solution to this problem is the continuous examination and development of the agricultural economy. In this study, matrix-assisted laser desorption/ionization time-of-flight mass spectrometer (MALDI -TOF MS) were used to analyse of sunflower, soybean and hemp. In order to analyse the protein of maize, this method has already been applied. However, for sunflower, soy and hemp, it is necessary to develop a sample preparation method. Choosing the optimal matrix solution for ionization the traget molecule is an essential part of developing the method. Our aim is to compare two different matrix solutions (α-HCCA, SA matrix), based on the properties (intensity, noise ratio, value of spectra) of the spectra.